2013
DOI: 10.4161/onci.23837
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a STAT3-dependent dendritic cell-derived CD14+cell population arising upon IL-10-driven maturation

Abstract: Interleukin (IL)-10 is a major cancer-related immunosuppressive factor, exhibiting a unique ability to hamper the maturation of dendritic cells (DCs). We have previously reported that IL-10 induces the conversion of activated, migratory CD1a+ DCs found in the human skin to CD14+CD141+ macrophage-like cells. Here, as a model of tumor-conditioned DC maturation, we functionally assessed CD14- and CD14+ DCs that matured in vitro upon exposure to IL-10. IL-10-induced CD14+ DCs were phenotypically characterized by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 47 publications
5
44
1
Order By: Relevance
“…Consistent with these tolerogenic qualities, IL-10-induced CD14 + macrophage-like MoDCs expressed high levels of immune suppression-related transcripts such as Indoleamine 2,3-dioxygenase (IDO), IL-4Rα, IL-6R, TGFβ1, HIF1α, and VEGFA (17). Activation of a HIF1α transcriptional signature has been reported in tumor-associated macrophages, even under normoxic conditions (36).…”
Section: Tumors Abuse DC Plasticity To Undermine Immunity: a Central mentioning
confidence: 92%
“…Consistent with these tolerogenic qualities, IL-10-induced CD14 + macrophage-like MoDCs expressed high levels of immune suppression-related transcripts such as Indoleamine 2,3-dioxygenase (IDO), IL-4Rα, IL-6R, TGFβ1, HIF1α, and VEGFA (17). Activation of a HIF1α transcriptional signature has been reported in tumor-associated macrophages, even under normoxic conditions (36).…”
Section: Tumors Abuse DC Plasticity To Undermine Immunity: a Central mentioning
confidence: 92%
“…Indeed, we and others have previously shown that monocyte-to-DC differentiation can be diverted to the development of M2-like cells in the presence of primary tumor supernatants, mostly due to high levels of prostaglandin-E2 (PGE2) and interleukin (IL)-6. 4 In primary cervical tumors, CD14 C cells are present in large quantities 5 , and can actually adopt a T cell-stimulatory M1-phenotype, which, in conjunction with CD8 C T cell infiltration, resulted in a prognostically favorable association with overall survival. Additionally, these M2-like cells expressed proangiogenic and pro-tumor invasive factors ( Fig.…”
mentioning
confidence: 99%
“…4 In primary cervical tumors, CD14 C cells are present in large quantities 5 , and can actually adopt a T cell-stimulatory M1-phenotype, which, in conjunction with CD8 C T cell infiltration, resulted in a prognostically favorable association with overall survival. 4 In cervical TDLN, we also found a clear and significant correlation between frequencies of Tregs and rates of CD14 C M2-like cells as well as their expression levels of PD-L1. 1 This is proof of early immune suppression in TDLN preceding actual metastatic spread and indicates the importance for tumor invasion of sabotaging effector T cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hematopoietic-specific deletion of the STAT3 gene results in an acute loss of conventional dendritic cells (cDCs) and attenuated responses to the Fms-related tyrosine kinase 3 ligand (Flt3L) in vivo (Laouar et al, 2003). The STAT3 signal enhanced CD14 + DC development (Lindenberg et al, 2013). Conversely, overexpression of STAT3 promoted DC maturation from hematopoietic progenitors (Onai et al, 2006).…”
Section: Introductionmentioning
confidence: 99%